Effect of milk protein content in Toddler formula on later BMI and obesity risk: protocol of the multicentre randomised controlled Toddler Milk Intervention (ToMI) trial - Berthold Koletzko; Veit Grote; Vanessa Jaeger; Joaquin Escribano; Marta Zaragoza; Mariona Gispert; Dominik Grathwohl (BMJ Open)
Introduction Reduction of milk protein content in infant formula provided during the first year of life has been shown to reduce early weight gain and obesity later in life. While rapid weight gain during the first 2 years of life is one of the strongest early predictors of obesity, the role of animal protein intake beyond the first year of life is unclear. The aim of this study is to examine the role of milk protein during the second year of life in healthy children on weight gain and obesity risk in preschool age.Methods and analysis This randomised, double-blinded study enrolled 1618 children aged 11.5–13.5 months in Spain and Germany into two groups receiving isocaloric toddler milk with differing protein content during the second year of life. The experimental formula contains 1.5 g/100 kcal and the control formula 6.15 g/100 kcal protein and otherwise equal formula composition, except for modified fat content to achieve equal energy density. The primary endpoint is body mass index (BMI)-for-age z-score at the age of 24 months adjusted for BMI at 12 months of age. The children are followed until 6 years of age.Ethics and dissemination Ethics approval was obtained from the ethical committees of the LMU University Hospital Munich, Germany (Nr. 555-15) and at Institut d’Investigació Sanitaria Pere Virgili, Reus, Spain (Ref. CEIm IISPV 013/2016). We aim at publishing results in peer-reviewed journals and sharing of results with study participants.Trial registration number NCT02907502.